Genetic polymorphisms in base excision repair in healthy Slovenian population and their influence on DNA damage - Erčulj, Nina (Acta chimica slovenica, 2010)
Genetic polymorphisms in DNA repair genes may result in altered DNA damage. The aim of our study was to determine the frequencies of common functional single nucleotide polymorphisms (SNPs) in specific base-excision DNA repair (BER) genes in healthy Slovenian population and evaluate their influence on DNA damage established by comet assay. In total 141 unrelated healthy subjectswere genotyped for hOGGl Ser326Cys, XRCCl Arg194Trp and Arg399Gln polymorphisms by real-time TaqMan assay. The frequencies of the hOGGl 326Ser/Ser, 326Ser/Cys and 326Cys/Cys genotypes were 63.8, 29.8, and 6.4%, respectively. The frequency distribution of XRCCl polymorphism was 88.7% for 194Arg/Arg, 9.2% for 194ArglTrp, 2.1 % for 194TrpITrp and 46.8% for 399Arg/Arg40.4% for 399Arg/Gln, 12.8% for 399Gln/Gln. The influence of selected BER polymorphisms on the percentage of comet tail DNA (% TD) was determined in a subgroup of 26 subjects. We found that% TD was significantly increased among individuals with hOGGl 326Ser/Cys heterozygous variant genotype as compared to 326SerlSer wild-type genotype (% TD = 8.9 4.2 vs. % TD = 6.9 1.4, P = 0.017). No significant associations between XRCCl Arg194Trp and Arg399Gln polymorphisms and% TD were found. Our results confirmed that DNA damage is modulated by hOGGl Ser326Cys polymorphism.
Keywords: DNA; genetski polimorfizem; genotip; poškodbe